A High‐Throughput Screening Method to Identify Compounds Displaying Human Vascular Embryonic Toxicity. (26th July 2019) - Rosa, Susana; Pitrez, Patrícia; Fernandes, Hugo; Ferreira, Lino
Abstract: This article describes a screening platform to identify compounds that affect human embryonic vascular development. The procedure comprises the generation of human embryonic‐like endothelial cells (ECs) from human pluripotent stem cells (hPSCs) and subsequent maturation under arterial flow conditions; the use of these cells for the high‐throughput screening of small molecules that specifically inhibit the survival of embryonic‐like ECs; the confirmation of the hits in embryonic‐like ECs cultured under flow shear stress; and final validation in mouse embryonic ECs. The embryonic‐like ECs express embryonic genes including DLL1, EPHB2, LYN, TEK, ID1, NRP2, CAST, FLT1, IGF1, DKK3, NIN, LEF1, and SORBS3 . The entire screening procedure (without the validation step) can be completed within 1 month. This platform is an alternative/complement to standard animal protocols for assessing the effects of chemicals on embryonic vascular development. © 2019 by John Wiley & Sons, Inc.